2012
DOI: 10.1155/2012/128608
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis in Acute Myeloid Leukemia and Opportunities for Novel Therapies

Abstract: Acute myeloid leukemia (AML) arises from neoplastic transformation of hematopoietic stem and progenitor cells, and relapsed disease remains one of the greater challenges in treating this hematologic malignancy. This paper focuses on angiogenic aspects of AML including the significance and prognostic value of bone marrow microvessel density and circulating cytokine levels. We show three general mechanisms whereby AML exploits angiogenic pathways, including direct induction of angiogenesis, paracrine regulation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 53 publications
(54 reference statements)
0
38
0
Order By: Relevance
“…6,7 Recent studies on the pathogenesis of AML showed that genetic disorder had the most important role in determining the response to chemotherapy and outcomes, which lead to the incorporation of targeted therapy into the standard treatment and open a new exciting era in AML therapy. Emerging agents include Gemtuzumab ozagamicin-targeting CD33, 8 histone deacetylase 9,10 and proteosome inhibitors, 11 antiangiogenesis agents, 12 Fms-like tyrosine kinase 3 inhibitors 9,13,14 and so on. MicroRNAs (miRNAs) are small non-coding RNAs that negatively regulate gene expression in the posttranscriptional level, [15][16][17] which have been identified as crucial regulators in normal and malignant biological processes.…”
mentioning
confidence: 99%
“…6,7 Recent studies on the pathogenesis of AML showed that genetic disorder had the most important role in determining the response to chemotherapy and outcomes, which lead to the incorporation of targeted therapy into the standard treatment and open a new exciting era in AML therapy. Emerging agents include Gemtuzumab ozagamicin-targeting CD33, 8 histone deacetylase 9,10 and proteosome inhibitors, 11 antiangiogenesis agents, 12 Fms-like tyrosine kinase 3 inhibitors 9,13,14 and so on. MicroRNAs (miRNAs) are small non-coding RNAs that negatively regulate gene expression in the posttranscriptional level, [15][16][17] which have been identified as crucial regulators in normal and malignant biological processes.…”
mentioning
confidence: 99%
“…AML is a hematological malignancy of the bone marrow characterized by a mutation in hematopoietic stem or progenitor cells, which develops into a highly proliferative accumulation of dysfunctional and immature myeloid cells (2). When interpreting studies on CECs and EPCs, attention must be paid to the different definitions and phenotypic characterization of CECs in each study, due to the lacking of a universal definition of these cell population (16), and to the different methods of CECs and EPCs detection, such as flow cytometry and the CELLSEARCH ® system (16).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been an increased understanding of the role of angiogenesis in the progression of AML (2). Although circulating endothelial cells (CECs) and their progenitors, endothelial progenitor cells (EPCs), were first described >30 years ago through light microscopy, the development of specific monoclonal antibodies against these cells has only recently provided the opportunity to investigate the pathophysiology of these cells (3).…”
Section: Introductionmentioning
confidence: 99%
“…Angiogenesis seems to be important for both leukemogenesis and susceptibility to intensive chemotherapy, and antiangiogenic strategies are therefore now being considered for the treatment of AML. [33][34][35] Though recently other mechanisms of action have also been reported, metronomic therapies are believed to work primarily through antiangiogenic mechanisms. [6,7] For the large group of elderly patients affected, intensive strategies are not possible because of high treatment-related mortality.…”
Section: Discussionmentioning
confidence: 99%